Shri Dhirubhai And Shri Mukesh Ambani at Patalganga - Reliance Industries Limited (2023)
Reliance sets up the first petrochemicals and polyester filament yarn plant in Patalganga in record time, demonstrating Founder-Chairman Dhirubhai Ambani’s belief in economies of scale and RIL Chairman and Managing Director Mukesh Ambani’s capability to execute world-class and global scale facilities ahead of schedule.